Генетична мінливість інтрогресивних ліній м’якої пшениці за геном бета-амілази - Наваліхіна, А.Г.; Антонюк, М.З.; Терновська, Т.К. (Фактори експериментальної еволюції організмів, 2014)
Aims. To explore electrophoretic spectra of beta-amylase in common wheat introgressive lines and explain the nature of spectra variability. Methods. PAAG, agarose gel electrophoresis, PCR, bioinformatical and statistical methods. Results. In beta-amylase electrophoretic spectra of introgressive wheat lines new components that were absent in the spectra of initial crosses, have appeared. Alleles encoding new components of the spectrum are members of allelic series of β-Amy-A1 and β-Amy-D1 genes. Three groups of lines that include introgressions from three Aegilops species do not differ in the frequency of changes in beta-amylase genes. Comparison of amplicon spectra after PCR showed pairs of primers that can be used to analyze changes in sequences of β-Amy-D1 and presumably, β-Amy-A1. Conclusions. Introgressive lines variability, that lies in the appearance of new components in electrophoretic spectra of beta-amylase has a genetic basis. It is associated with changes in gene sequences of β-Amy-D1 and conceivably, β-Amy-A1.